(untitled) (Law and world, 2024)
The presented article represents an attempt to assess the possibility and perspectives of considering AI-generated works as artworks and objects of museum exhibitions in the European Union. The purpose of the work is to assess whether AI-generated works can be recognized as artwork and if such works can be placed at museums or, on the contrary, if museums are eligible to exhibit and protect works that do not match the definition of the artwork. For the purposes of the article, legal definitions of the artwork and AI are primarily explored to detect possible authorship and legal subjectivity of the artificial intelligence. Accordingly, the next core topic of discussion is the capacity of museums to maintain ai-generated works explored from the perspective of the definition and purpose of museums as institutions. The article contains reasoning and assumptions regarding possible scenarios of the authorship of AI and prognoses about awaited legal challenges in the near future. Not all questions raised by the author are met with unambiguous answers, and they are left open for discussion until further development of legal frameworks and case law acquires a certain direction. Keywords: Artificial Intelligence, AI-generated works, Artwork, AI and copyright, AI as the subject of law, Museums, and AI. Introduction The development of Artificial Intelligence (AI) and the dynamic of increasing the realistic character of artworks created using AI gives the basis to expect that besides obtaining popularity among lovers of reproductions, in the nearest future, the issue of considering AI-generated works as artworks will become a topic of frequent discussions. Consequently, the discussion about the legal and ethical aspects of exhibiting such works acquires further relevance. This issue can be especially vulnerable for the museums and galleries, as they set their reputation at risk in case of providing wrong data about the legal status of the item and related copyright, and such actions may also contradict their essential objectives. The article is drafted based on the hypothesis that AI-generated works should not be considered artworks, accordingly, they should not be objects of the same legal protection and not safeguarded by the museums. The presented article aims to explore the challenges of detecting the legal nature of AI-generated works to draft effective recommendations based on the Common European legal framework for museums to tackle the challenge efficiently. Accordingly, the final product will serve as material for further scientific research and as a guideline for corresponding art institutions or lawyers in the field. The article will primarily concentrate on doctrinal methods of research, especially on exploring the caselaw of the Court of Justice of the European Union (CJEU) and corresponding legal frameworks or policy documents. Besides, the methods of analysis and synthesis will also be applied to draft some assumptions and recommendations. Additionally, comparative analysis will serve for a diverse and comprehensive exploration of the topic. 1. AI as Subject of Law Regarding Copyright Detection of the legal status of AI-generated works is directly connected to defining the legal notion of the artwork itself and the probability of considering AI as the subject of legal transactions. 1.1. The Notion of Art and Artwork in the EU Defining the legal notion of the artwork and art is a key pre-step of effective detection of the legal status of the creator of the artwork. The terms “art” and “artwork” do not have universal legal definitions in the EU, but their essence can be detected in various legal acts. For example (f.e.), the early Directive 2001/84/EC under the term “original work of art” considers works of graphic or plastic art such as pictures, collages, paintings, drawings, engravings, prints, lithographs, sculptures, tapestries, ceramics, glassware, and photographs, provided they are made by the artist himself or are copies considered to be original works of art.[1] The same directive also defines that those copies of works of art covered by this Directive, which have been made in limited numbers by the artist himself or under his authority, shall be considered to be original works of art for the purposes of this Directive. Such copies will normally have been numbered, signed, or otherwise duly authorized by the artist. [2] It is worth noting that Directive 2001/29 also admits and protects reproduction rights but considers works created by human authors under the field of protection (“Member States shall provide for the exclusive right to authorize or prohibit direct or indirect, temporary or permanent reproduction by any means and in any form, in whole or in part”… for participants of the legal transaction described by the directive),[3] and grants the authors with exclusive rights related to the exhibition of their works (Member States shall provide authors with the exclusive right to authorize or prohibit any communication to the public of their works, by wire or wireless means, including the making available to the public of their works in such a way that members of the public may access them from a place and at a time individually chosen by them (§1). Member States shall provide for the exclusive right to authorize or prohibit the making available to the public, by wire or wireless means, in such a way that members of the public may access them from a place and at a time individually chosen by them... (§2)).[4] Artwork may also belong to the category of cultural goods, as according to the Regulation (EU) 2019/880, “cultural goods” means any item which is of importance for archaeology, prehistory, history, literature, art, or science (art. 2, cl. 1), particularly objects of artistic interest, such as pictures, paintings and drawings produced entirely by hand on any support and in any material (excluding industrial designs and manufactured articles decorated by hand); original works of statuary art and sculpture in any material; original engravings, prints and lithographs; original artistic assemblages and montages in any material.[5] The interesting reasoning is provided by the CJEU in the judgment Infopaq International A/S v. Danske Dagblades Forening, declaring that “Copyright within the meaning of Article 2(a) of Directive 2001/29 is liable to apply only in relation to a subject matter which is original in the sense that it is its author’s intellectual creation. As regards the parts of a work, they are protected by copyright since, as such, they share the originality of the whole work. The various parts of a work thus enjoy protection under that provision, provided that they contain elements which are the expression of the intellectual creation of the author of the work.”[6] The Court derived from the provisions of the Berne Convention and mentioned that the protection of certain subject matters as artistic or literary works presupposes that they are intellectual creations.[7] According to the judgment, the Berne Convention declares that the expression “literary and artistic works” shall include every production in the literary, scientific, and artistic domain, whatever may be the mode or form of its expression, such as … works of drawing, painting, architecture, sculpture, engraving, and lithography; photographic works to which are assimilated works expressed by a process analogous to photography; works of applied art; illustrations, maps, plans, sketches and three-dimensional works relative to geography, topography, architecture or science.[8] Later, in 2019, the court mentioned that the original artworks reflect the personality of its author as an expression of the author’s free and creative choices.[9] Some answers and interpretations can be found in the relevant caselaw of the CJEU. In the judgment Levola Hengelo BV v. Smilde Foods BV. (2018), the court evolved reasoning that two cumulative conditions must be satisfied for subject matter to be classified as a work within the meaning of Directive 2001/29 (§35). First, the subject matter concerned must be original in the sense that it is the author’s intellectual creation… (§36), secondly, only something that is the expression of the author’s intellectual creation may be classified as a ‘work’ within the meaning of Directive 2001/29 (§37).[10] Using creatures of technology by the authors does not exclude them from the circle of artworks. F.e., CJEU admits that a photograph may be protected by copyright if it is the intellectual creation of the author reflecting his personality and expressing his free and creative choices in the production of that photograph.[11] The identic approach is formed by the courts of Common Law countries. F.e., in Case Thaler v. Perlmutter, the District Court of Columbia formed a reasoning that “Copyright is designed to adapt with the times. Underlying that adaptability, however, has been a consistent understanding that human creativity is the sine qua non at the core of copyrightability, even as that human creativity is channeled through new tools or into new media… for example, the photographs amounted to copyrightable creations of “authors,” despite issuing from a mechanical device that merely reproduced an image of what is in front of the device because the photographic result nonetheless “represent[ed]” the “original intellectual conceptions of the author.” A camera may generate only a “mechanical reproduction” of a scene but does so only after the photographer develops a “mental conception” of the photograph, which is given its final form by that photographer’s decisions like “posing the [subject] in front of the camera, selecting and arranging the costume, draperies, and other various accessories in the said photograph, arranging the subject to present graceful outlines, arranging and disposing of the light and shade, suggesting and evoking the desired expression, and from such disposition, arrangement, or representation” crafting the overall image”.[12] High-presented legal notions define art and artworks as a materialized expression of human consciousness and feelings that can describe the personal attitude of the artist to various aspects of social life. The social value and function of the artwork are wider than is prescribed by various legal acts, and it is primarily determined by the purpose and the main idea of the artwork that the author aimed to express via the artwork directly or using allegories. In the “Manifesto on the Freedom of Expression of Arts and Culture in the Digital Era” it is mentioned that “…experts and cultural professionals who hint at problems, spell out uncomfortable truths, speak the unspoken and make the unseen visible – using their artistic and cultural means and creating spaces for societal debate within and beyond the mainstream bodies of political discourse and in social media.”[13] 1.2. AI as a Potential Creator of the Artwork From the perspective of a comprehensive analysis of the topic, the definition of AI is also worth being distinguished. It can be found in various legal acts. For example, the CoE Framework Convention on AI and Human Rights and Democracy and the Rule of Law defines an “artificial intelligence system” as a machine-based system that, for explicit or implicit objectives, infers, from the input it receives, how to generate outputs such as predictions, content, recommendations or decisions that may influence physical or virtual environments.”[14] Deriving from the legal notion of “artwork”, the opportunity of considering AI as a creator of the artwork practically equals zero, but such a condition may be changed, as the existing legal point of view is determined by various circumstances, including the fact that the legal notion of the “artwork” represents a traditional, conservative approach formed in the era, when gadgets could not have been believed to be self-governing performers of some tasks. Additionally, it can be affected by the extremely cautious attitude of the judiciary to restrain from evolving such reasoning, where AI can be described as a potential participant in legal transactions. However, an overview of legal history contains epochs when different subjects or objects were considered to be participants of legal transactions or, on the contrary, excluded from such a group. F.e., in the early development of human society, objects and animals used to be “found guilty” and sentenced to various penalties, while representatives of certain classes of the society were considered to be equal to things and deprived of their rights. Quite a lot of such examples can be found in the legal history of ancient Rome, Greece, Egypt, etc. On the contrary, the development of economic relations caused the creation of legal entities, but such news was widely rejected by distinguished representatives of legal society as they could not imagine non-human beings as legal actors, even though even Ulpian used to be an author of the first concepts of legal entities in the II-III centuries A.C., already used to write unions like legal entities. Currently, legal entities represent almost full-fledged participants in legal transactions and subjects of essential human rights according to their applicability. F.e., Sunday Times v. the United Kingdom was the first case where the European Court of Human Rights (ECHR) found a violation of the Freedom of Expression (Art. 10) against the legal entity. In later judgments, the Court referred to issues of protecting dissemination systems, including oral, printed form, radio broadcast, painting, and other forms of expression.[15] Recognition of AI as a subject of law is more challenging, especially when AI-governed machines in an existing form lack the component of personality,[16] but besides the existence of the uniform case law, the discussion about the legal subject status of AI demonstrates growing interest from legal scientists. According to one of the viewpoints detected in legal literature, „personality is established when a legal assumption is updated in reality as long as it is foreseen in a general norm of law that describes a determined situation of fact where the subject or undetermined person is, with the purpose to individualize it as a holder of determined rights or certain obligations in a specific juridical relationship”. Besides, the modern challenge of discussing AI-powered gadgets as “participants” of legal transactions keeps being an upcoming topic of discussion, some more circumstances may be revealed to assess the possibility of declaring AI as a potential creator of the artwork. The uniform case law of the CJEU set the tendency that an intellectual creation should reflect the author’s personality (§88). So, the author should be able to express his creative abilities in the production of the work by making free and creative choices (§89).[17] So far, unless a unified caselaw develops clear reasoning about possible scenarios of acknowledging AI as a potential subject of law, evolving an unambiguous hypothesis is quite difficult, especially if considering the point of view of various scientists, who highlight the impossibility of the creation of fluent artificial intelligence, as the essence intelligence cannot be understood completely.[18] However, the modern approach is reasonably different, and signs of possible recognition of AI as a subject of law are detected in some legal provisions. Primarily should be distinguished two legal acts within the jurisdiction of the EU they are the so-called Resolution on Civil Law Rules of Robotics and the so-called AI Act[19], which was adopted recently. The first legal act calls on the Commission to create a specific legal status for robots that make autonomous decisions or otherwise interact with third parties independently. According to the act, the European Parliament calls on the Commission, when carrying out an impact assessment of its future legislative instrument, to explore, analyze, and consider the implications of all possible legal solutions, such as creating a specific legal status for robots in the long run, so that at least the most sophisticated autonomous robots could be established as having the status of electronic persons responsible for making good any damage they may cause, and possibly applying electronic personality to cases where robots make autonomous decisions or otherwise interact with third parties independently.[20] The second and the newest international legal act is the so-called AI Act, which represents a combination of several legal acts and creates a general legal platform. According to the interview with Secretary General of the Council of Europe Marija Pejčinović, expectations towards the AI Act are quite high as this should serve as the first universal legal framework regulating the sphere. According to the words of the Secretary General of the Council of Europe, “the text strikes the right regulatory balance precisely because it has benefitted from the input of governments and experts, and industry and civil society… After its adoption by the Committee of Ministers in the coming weeks, countries from all over the world will be eligible to join it and meet the high ethical standards it sets”.[21] Considering the arguments enumerated by the courts and the specifics of the creation of works by AI comes a legitimate expectation that in the near future, the issue will acquire a more problematic character. European Parliament’s 2020 Report on AI and Intellectual Property Rights also admits that AI challenges the traditional understanding of artwork, and it may be the object of further discussions.[22] The supporters of declaring AI-generated work as artwork may base their opinion on the argument that creating objects by AI also needs human participation, as humans are the ones who draft a description of the product expected from the AI-governed machine. In such a composition of the circumstances, AI creates a work based on a human mindset. The potential object of discussion may become cases when AI with a certain level of autonomy of the software generates a painting according to the instructions of a human. Like the case with photography, when a managing human can have a theoretical opportunity to use software to administer the process of generating works by AI. The question is how the level of human involvement in the process of forming the final work should be measured and if such outcomes can be predicted by the humans while forming the instructions for the AI-powered gadget. The above-mentioned topic should also be left open unless the corresponding political will of developing such legal institutes becomes relevant and the ability of humans to predict features of AI-generated products can be assessed by corresponding technical inspection. From the perspective of museums, such theoretical reasoning is less important at the moment but represents an issue of raising relevance, so it is worth mentioning. 2. Capacity of the Museums to Exhibit AI-generated Works Finding solutions for modern legal problems requires up-to-date solutions. Legislation may lack the existence of provisions designed in a manner that newly raised circumstances could be foreseen. Such a situation is detected regarding the exhibition and protection of AI-generated works by the museums. The existing legal framework of the EU does not contain direct provisions referring to the high-distinguished issue, but certain norms could be interpreted regarding the question. First of all, the term “museum” should be defined because besides the traditional understanding of museums, so-called digital display museums also do exist, and the concept of their work is reasonably different from the classic understanding. Such museums represent organizations that provide 2D or 3D shows for the customers and display the works in digital reality. As a rule, such museums exist independently, but the combinations of traditional and digital display museums are also quite frequent. According to the definition of a museum formed by the Museums Association in 1998, “Museums enable people to explore collections for inspiration, learning, and enjoyment. They are institutions that collect, safeguard and make accessible artifacts and specimens, which they hold in trust for society”.[23] In 2022, the International Council of Museums (ICOM) approved the proposal for the new definition of a museum. It defines that “A museum is a not-for-profit, permanent institution in the service of society that researches, collects, conserves, interprets and exhibits tangible and intangible heritage. Open to the public, accessible, and inclusive, museums foster diversity and sustainability. They operate and communicate ethically, professionally and with the participation of communities, offering varied experiences for education, enjoyment, reflection and knowledge sharing.” [24] It deserves mentioning that ICOM was one of the first organizations that raised an issue of the need for a legal definition of a museum because that seemed relevant both from the perspectives of law and ethics. [25] According to the definition and corresponding legal framework, museums are eligible to organize not only physical but also digital and online exhibitions. Directive (EU) 2019/790, also known as (the DSM Directive), states that “an online content-sharing service provider shall therefore obtain authorization from the rightsholders referred to in Article 3(1) and (2) of Directive 2001/29/EC, for instance by concluding a licensing agreement, to communicate to the public or make available to the public works or other subject matter”.[26] The directive determines authorization of an online content-sharing service provider as a mandatory part of their activities. Such authorization can be done in various ways, including by concluding a licensing agreement. [27] While discussing the purposes of museums, two basic aspects should be distinguished: the role of a museum in safeguarding artworks and the mission of connecting society to art. From the perspective of the second objective, the opinion is that AI-generated works may be placed in museums to serve as an attraction for society and encourage them to see real masterpieces of art. This kind of reasoning may seem admissible, but it meets the ethical dilemma and a threat of promoting works that do not represent artworks, respectively, it contradicts the fundamental purpose of the museum and may lead to increasing interest in works that miss the main component of the artwork - a cultural value. The issue of so-called AI museums also requires attention, and it may be an object of separate research, but the presented article cannot fully bypass this topic. Despite having similar names, so-called AI museums do not necessarily describe identic institutions, accordingly, they do not necessarily serve the same purpose and values as museums do. Duplication of terms in various legal relations with different meanings is quite frequent, but such a mix of terms should not lead society to misrepresentation. To make an interim summary, museums, as not-for-profit organizations, represent institutions first of all serving values. They are not prohibited from using AI for achieving their purposes, but in such a manner that it supports the accomplishment of the main objectives of museums, not distancing from them. Conclusion and Recommendations The fundamental purpose of the museums and museum-kind galleries should be formulated based on the core characteristic feature of ensuring the safety and accessibility of the examples of cultural heritage, fine arts, and distinguished creatures of contemporary art. Respectively, derived from the legal, historical, and social contest, museums represent institutions responsible for keeping the advanced creatures of human creativity and granting society access to such masterpieces. The highly-discussed precedents and related reasonings demonstrated that the allowance of safeguarding and exhibiting artworks created using artificial intelligence represents an issue combining legal and ethical challenges. As discussed in Chapter 1, the unified legislative approach excludes the possibility of authorship by the objects of law, including AI, and such a point of view is shared by the courts worldwide while interpreting the legal notion of artwork. However, the number of mentions in legislation, official reports, and several precedents where certain general reasonings leave space for further expectations create an impression that the attitude could be changed. In the context of museums, so far, no legal framework directly prohibits exhibiting artworks created by AI if the corresponding information is properly delivered to the target society. Besides the fact that the universal legal acts set legal frameworks for the museums, the EU member states keep the right to design further local regulations, but they should not contradict international standards. In such a configuration of legal provisions and related legitimate interest towards museums, so far, I consider that the conservative approach should be supported, at least unless the legal definition of the artwork gets modified and AI-made products appear in the circle of artworks and fruits of intellectual property. Additionally, the specifics of the creation of the artworks and specific characteristics of products made by the AI should be highlighted. The artwork itself represents a fruit of human creativity; it is a unique product, and even in the case of re-production, it keeps its unique character, as reproduction is also a visual demonstration of the creator’s mind. The AI-generated products should be considered as items of serial production with an option of making exact copies, so unless a work is a single item and done by human engagement, it shouldn’t be accepted as an artwork. The abovementioned attitude should not be assessed as a reduction of accessibility of works made by AI to the market, but the segmental division is a necessity. The artworks, with the traditional understanding of this term, as manifestations of human creativity should keep their place in cultural surroundings and be objects of special care by the museums. In my personal belief, the same regard should not be extended to AI-generated works. Primarily because they simply do not match the legal definition of the artwork, and as it is already formulated above, it lacks the essential component of uniqueness and demonstration of human creativity. Finally, AI-generated products as objects of potential massive production with the ability to create exact copies drop out of the concept of artworks and objects with cultural value so that despite the level of attractiveness and quality, they still cannot be accepted as artworks. Bibliography: Scientific Materials: Adriano, E.A.Q. (2015). The Natural Person, Legal Entity or Juridical Person and Juridical Personality, Penn State Journal of Law & International Affairs, 4(1); Davies, C. R. (2011). An Evolutionary Step in Intellectual Property Rights - Artificial Intelligence and Intellectual Property, Computer Law & Security Review, 27(6); Mendel, T. (2016). Freedom of Expression: A Guide to the Interpretation and Meaning of Article 10 of the European Convention on Human Rights. Bibliography Case Law: Court of Justice of the European Union. (2019, September 12). Cofemel – Sociedade de Vestuário SA v G-Star Raw CV, C-683/17, §30; Court of Justice of the European Union. (2011, December 1) Eva-Maria Painer v. Standard VerlagsGmbH and Others, No. C-145/10; Court of Justice of the European Union. (2011, October 4). Football Association Premier League LTD and Others v QC Leisure and Others (C-403/08) and Karen Murphy v Media Protection Services Ltd, No. C-429/08. Court of Justice of the European Union. (2009, June 16). Infopaq International A/S v. Danske Dagblades Forening, No. C-5/08; Court of Justice of the European Union. (2018, August 7). Land Nordrhein-Westfalen v Dirk Renckhoff, No. C-161/17; Court of Justice of the European Union. (2018 November 13) Levola Hengelo BV v. Smilde Foods BV, No. C-310/17; Court of Justice of the European Union. (1979, April 26). Sunday Times v. the United Kingdom, No. 6538/74; S. District Court for the District of Columbia. (2023, August 18). Thaler v. Perlmutter, No. 22-CV-384-1564-BAH. Legal Acts: Berne Convention for the Protection of Literary and Artistic Works, Paris. (1971); Council of Europe Framework Convention on Artificial Intelligence and Human Rights, Democracy and the Rule of Law, CETS 225, EU. (2024); European Parliament & Council. (2001). Directive 2001/29/EC of the European Parliament and of the Council of 22 May 2001 on the Harmonisation of Certain Aspects of Copyright and Related Rights in the Information Society, EU; European Parliament & Council. (2001). Directive 2001/84/EC of the European Parliament and of the Council of 27 September 2001 on the Resale Right for the Benefit of the Author of an Original Work of Art, EU; Directive 2019/790 of the European Parliament and of the Council of 17 April 2019 on Copyright and Related Rights in the Digital Single Market and Amending Directives 96/9/EC and 2001/29/EC. (2019). EU; European Parliament Resolution of 16 February 2017 with Recommendations to the Commission on Civil Law Rules on Robotics (2015/2103(INL)), (2018/C 252/25), EU. (2017); Regulation 2019/880 of the European Parliament and of the Council of 17 April 2019 on the Introduction and the Import of Cultural Goods, EU. (2019); Regulation 2024/1689 of the European Parliament and of the Council of 13 June 2024 laying down Harmonised Rules on Artificial Intelligence and Amending Regulations (EC) No 300/2008, (EU) No 167/2013, (EU) No 168/2013, (EU) 2018/858, (EU) 2018/1139 and (EU) 2019/2144 and Directives 2014/90/EU, (EU) 2016/797 and (EU) 2020/1828 (Artificial Intelligence Act) (Text with EEA relevance), EU. (2024); Other Resources: Cornu, M., (2020), Thinking of the Museum as a Legal Category: What are the Issues Around Definition? <https://www.icom-musees.fr/sites/default/files/media/document/2020-05/Traduction%20Marie%20Cornu_reluCLS.pdf> (Last accessed: 30.11.2024); EEIG EU Standard for Museums and Galleries, EU. (2012); Pejčinović, M. (2024, March 15). Interview with the Secretary General of the Council of Europe. Artificial Intelligence, Human Rights, Democracy, and the Rule of Law Framework Convention. Council of Europe <https://www.coe.int/en/web/artificial-intelligence/-/artificial-intelligence-human-rights-democracy-and-the-rule-of-law-framework-convention> (Last accessed: 30.11.2024); Manifesto on the Freedom of Expression of Arts and Culture in the Digital Era, EU. (2020); Proposal for the definition of the museums by the ICOM<https://icom.museum/en/resources/standards-guidelines/museum-definition/> (Last accessed: 30.11.2024); Report on Intellectual Property Rights for the Development of Artificial Intelligence Technologies, EU. (2020). Footnotes [1] European Parliament & Council. (2001). Directive 2001/84/EC of the European Parliament and of the Council of 27 September 2001 on the Resale Right for the Benefit of the Author of an Original Work of Art, EU, Article 2 (Clause 1). [2] Ibid, Art. 2, Cl. 2. [3] European Parliament & Council. (2001). Directive 2001/29/EC of the European Parliament and of the Council of 22 May 2001 on the Harmonisation of Certain Aspects of Copyright and Related Rights in the Information Society, EU, Art. 2. [4] Ibid, Art. 3, §§1-2. [5] European Parliament & Council. (2019). Regulation 2019/880 of the European Parliament and of the Council of 17 April 2019 on the Introduction and the Import of Cultural Goods, EU, Art. 2, Cl. 1 & Annex 1, cl. “g”. [6] Court of Justice of the European Union. (2009, June 16). Infopaq International A/S v. Danske Dagblades Forening, No. C-5/08, Summary of the Judgement, §1. [7] Ibid, §34. [8] Berne Convention for the Protection of Literary and Artistic Works, Paris. (1971). Art. 2, § 1. [9] Court of Justice of the European Union. (2019, September 12). Cofemel – Sociedade de Vestuário SA v G-Star Raw CV, No. C-683/17, §30. [10] Court of Justice of the European Union. (2018, November 13). Levola Hengelo BV v. Smilde Foods BV, No. C-310/17, §§35-37. [11] Court of Justice of the European Union. (2018, August 7). Land Nordrhein-Westfalen v Dirk Renckhoff, No. C-161/17, §14. [12] U.S. District Court for the District of Columbia. (2023, August 18). Thaler v. Perlmutter, No. 22-CV-384-1564-BAH, p. 8. [13] European Union. (2020). Manifesto on the Freedom of Expression of Arts and Culture in the Digital Era, §3. [14] Council of Europe Framework Convention on Artificial Intelligence and Human Rights, Democracy and the Rule of Law, 2024, CETS 225, EU, Art. 2. [15] Mendel, T. (2016). Freedom of Expression: A Guide to the Interpretation and Meaning of Article 10 of the European Convention on Human Rights. P. 6; and European Court of Human Rights. (1979, April 26). Sunday Times v. the United Kingdom, No. 6538/74, §§42-68. [16] Adriano, E. A. Q. (2015). The Natural Person, Legal Entity or Juridical Person and Juridical Personality, Penn State Journal of Law & International Affairs, 4(1). P. 384. [17] Court of Justice of the European Union. (2011, December 1). Eva-Maria Painer v. Standard VerlagsGmbH and Others, No. C-145/10, §§87-89 with further reference on Court of Justice of the European Union. (2011, October 4). Football Association Premier League LTD and Others v QC Leisure and Others (C-403/08) and Karen Murphy v Media Protection Services Ltd, No. C-429/08. [18] Davies, C. R. (2011). An Evolutionary Step in Intellectual Property Rights - Artificial Intelligence and Intellectual Property, Computer Law & Security Review, 27(6). P. 619. [19] Regulation 2024/1689 of the European Parliament and of the Council of 13 June 2024 laying down Harmonised Rules on Artificial Intelligence and Amending Regulations (EC) No 300/2008, (EU) No 167/2013, (EU) No 168/2013, (EU) 2018/858, (EU) 2018/1139 and (EU) 2019/2144 and Directives 2014/90/EU, (EU) 2016/797 and (EU) 2020/1828 (Artificial Intelligence Act) (Text with EEA relevance), EU. (2024). [20] European Parliament Resolution of 16 February 2017 with Recommendations to the Commission on Civil Law Rules on Robotics (2015/2103(INL)), (2018/C 252/25), EU, (2017), §59, Cl. “f”. [21] Pejčinović, M. (2024, March 15). Interview with Secretary General of the Council of Europe. Artificial Intelligence, Human Rights, Democracy, and the Rule of Law Framework Convention. Council of Europe <https://www.coe.int/en/web/artificial-intelligence/-/artificial-intelligence-human-rights-democracy-and-the-rule-of-law-framework-convention> (Last accessed: 30.11.2024). [22] European Union. (2020). Report on intellectual property rights for the development of artificial intelligence technologies, Explanatory statement. [23] EEIG EU Standard for Museums and Galleries, EU. (2012). P. 1. [24] Information on the official webpage of ICOM <https://icom.museum/en/resources/standards-guidelines/museum-definition/> (Last accessed: 30.11.2024). [25] Cornu, M. (2020). Thinking of the Museum as a Legal Category: What are the Issues Around Definition? <https://www.icom-musees.fr/sites/default/files/media/document/2020-05/Traduction%20Marie%20Cornu_reluCLS.pdf> (Last accessed: 30.11.2024). [26] Directive 2019/790 of the European Parliament and of the Council of 17 April 2019 on Copyright and Related Rights in the Digital Single Market and Amending Directives 96/9/EC and 2001/29/EC, (2019), EU, Art. 17, §1. [27] Ibid, Art. 17, §2.